School Literacy Movement Program Through Reading Corner In Elementary Schools - Antartika, Shella Shinta; Muhroji, Muhroji (Universitas Pakuan, 2025)
The purpose of this study was to: 1. Describe the implementation of the School Literacy Movement Program through the Reading Corner; 2. Describe the supporting and inhibiting factors for the implementation of the School Literacy Movement Program through the Reading Corner; and 3. Identify effective solutions to improve the success of the School Literacy Movement Program through the Reading Corner. Descriptive qualitative research was used. The object of the study was related to the implementation of the School Literacy Movement through the Reading Corner. The subjects of the study included the principal, vice principal for curriculum, homeroom teacher, and students. Data collection techniques included observation, interviews, and documentation. triangulation of sources and techniques to evaluate the reliability of information. Data reduction, data presentation, and drawing conclusions are all included in the category of interactive data analysis. The results of the study show that: 1. The Reading Corner at SD Aisyiyah Unggulan Gemolong has succeeded in increasing students' interest in reading and building a sustainable literacy culture through the implementation of the School Literacy Movement (GLS) Program, 2. The success of the program is supported by active student involvement, collaboration between teachers, and community contributions, but is constrained by limited book collections, minimal teacher training, and lack of budget allocation, especially during the pandemic, and 3. The proposed solutions include improving the quality and quantity of books, involving parents and communities, developing varied activities, utilizing technology, establishing literacy clubs, and routine program evaluations.